Cowper's Syringocele Causing Painful Haematuria in an Adult - Matthew B.K. Shaw; Owen Cole; Timothy R. Terry (The Scientific World Journal)
A Cowper's syringocele in an adult is rare. Ten cases are reported in the world literature. The authors report a case of painful haematuria due to the presence of a Cowper's syringocele in an adult. The classification of lesions of the Cowper's gland is discussed together with common symptoms and differential diagnosis.